Estudo prospectivo de ultrassonografia em pacientes com artrite idiopática juvenil em remissão clínica: a sinovite subclínica pode predizer reativação da doença? - Silva, Vanessa Bugni Miotto e [UNIFESP] (2016)
Introduction: Joint ultrasound (US) studies of patients with juvenile idiopathic arthritis (JIA) in clinical remission demonstrate the presence of subclinical synovitis and positive Power Doppler (PD) signal. The significance of these findings is not yet well understood. Objectives: To assess whether the changes detected by US in a group of patients with JIA in clinical remission can predict disease flare and to evaluate possible factors associated with flare and joint damage over 30 months of follow-up. Methods: Clinical/laboratory assessment: physical examination in 34 joints, functional capacity and inflammatory markers. Sonographic evaluation: synovitis, PD signal and erosion in 34 joints (60 recesses). Subclinical synovitis was defined when there was synovitis and/or positive PD signal in US joints of patients in clinical remission. Flare was defined as any joint presenting arthritis on physical examination requiring therapy modification. Results: Total of 35 patients, 28 (80%) girls, 14 (40%) of the persistent oligoarticular subtype, 12 (34.3%) extended oligoarticular, 9 (25.7%) polyarticular and 26 (74.3%) in remission on medication. At baseline, the mean age of patients was 11.6 ± 3.8 years, the age of JIA onset was 4.4 ± 3.2 years, the disease duration was 7.1 ± 3 5 years, and time of disease remission was 1.9 ± 2.2 years. Of the 35 patients evaluated, 20 (57.1%) flared. There were no clinical or ultrasound differences among patients with and without flare. Regarding the assessment of joint after 6 and 12 months of sonographic evaluation, 70 / 3,162 (2.2%) and 80 / 2,108 (3.8%) of the joints flared, respectively. Joints with subclinical synovitis and positive PD signal flared more after 6 and 12 months. Joint damage (erosion) was evaluated in 2,108 joints and 25 (1.2%) showed erosion over time. Joints with subclinical synovitis showed more erosion. The risk of flare was five times higher in patients with positive PD signal and 14 times higher in patients in remission on medication. Conclusion: The presence of PD signal and remission on medication determined increased risk of JIA flare. Joints with subclinical synovitis and positive signal PD flared more over 12 months and joints with subclinical synovitis presented more erosion over time. Patients in remission on medication and positive PD signal evaluated by US should postpone the reduction or suspension of medication due to the risk of flare. The joints with subclinical synovitis or positive PD signal should be monitored more closely due to the risk of flare and long-term joint damage.